Manganese zinc ferrite material and preparation method thereof
Manganese-Zinc ferrite materials treated with specific formulas and processes solve the problem of low magnetic permeability under wide temperature conditions, achieve high magnetic permeability and high Curie temperature, and improve the material's common mode filtering in automotive electronics and anti-EMI stability in the device.
Patent Information
- Application Number
- CN202411268457.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
The existing manganese-zeb ferrite materials have low magnetic permeability under wide temperature conditions, and cannot take into account both high magnetic permeability and high Curie temperature, which affects its working stability in the automotive electronics field and in anti-EMI common mode filters.
Using specific formulas of manganese-zeb ferrite materials, including main components Fe2O3, ZnO and MnO, auxiliary components CoO, CaO, Bi2O3 and MoO, the components are regulated by sol-gel method and sintering process, and the magnetic properties of the material are improved. Conductivity and Curie temperature.
Within a wide temperature range of 0 to 145℃, the material has an initial magnetic permeability of ≥12000 and a low temperature coefficient. The magnetic permeability does not drop at high frequency, and the Curie temperature is >145℃, which significantly improves the material in automotive electronics and anti-EMI Working stability in the field of common mode filters.
Smart Images

Figure BDA0005037902940000181 
Figure BDA0005037902940000191 
Figure BDA0005037902940000192
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of manganese-zinc ferrite materials, and in particular to a manganese-zinc ferrite material and a preparation method thereof. Background Art
[0002] High magnetic permeability manganese-zinc ferrite materials are widely used in the fields of electronic signal transmission, anti-electromagnetic interference technology, environmental protection and energy saving, and the automotive electronics market. When manganese-zinc ferrite materials are used in electronic products and devices, they need to have relatively high comprehensive performance. For example, in the field of automotive electronics, wide temperature, wide frequency and high magnetic permeability manganese-zinc soft magnetic ferrite materials are required. If a car is fully loaded in a hot area and needs to be parked, the heat dissipated from the exhaust pipe will make the engine room temperature as high as 100°C or above. If it is in a cold area, the outdoor temperature is as low as -40°C. Therefore, in extreme weather, it is necessary to ensure that the automotive ferrite material has excellent temperature characteristics and the magnetic permeability is stable and low during normal operation. The current research focuses on how to optimize the formula of manganese-zinc ferrite materials and develop matching processes to obtain manganese-zinc ferrite materials with high magnetic permeability, high Curie temperature, wide frequency and wide temperature.
[0003] Patent CN104961450A discloses a wide temperature range and high initial permeability soft ferrite material, the main components of which are 47.5-54.5 mol% iron oxide, 15-24 mol% zinc oxide, and 27.4-30.5 mol% manganese oxide. In the temperature range of -40-85°C, the initial permeability is above 2900, which broadens the magnetic working range of the ferrite material. However, its permeability is far lower than 5000, and there is still a relatively low permeability, and its Curie temperature Tc is not mentioned.
[0004] CN106747396A discloses a high magnetic permeability manganese-zinc ferrite material for automotive electronics and a preparation method thereof, wherein the main components are 52.0-53.0 mol% iron oxide, 17.0-20.5 mol% zinc oxide, and the rest is manganese oxide, and the auxiliary materials are analytically pure CuO, CaO, Ta2O5, In2O3 and Bi2O3, and within the temperature range of 25°C to 80°C, the valley point between the second peak and the first peak of the magnetic permeability is greater than 8000, and the Curie temperature Tc is greater than 150°C. Although the Curie temperature Tc is greater than 150°C, under wide temperature conditions, the magnetic permeability is still relatively low, and it is impossible to take into account both the higher Curie temperature and the higher magnetic permeability.
[0005] CN101050108A discloses a broadband, low-loss, high-permeability manganese-zinc ferrite material and a preparation method thereof, wherein the main components include 21.5-26.5 mol% manganese oxide, 20.5-25.5 mol% zinc oxide, the rest is iron oxide, and the auxiliary components include any one of sodium oxide and potassium oxide, bismuth oxide, molybdenum oxide and vanadium oxide. Although the initial permeability of the prepared material at 25°C and 10kHz is 12000 or more, it can only ensure that the permeability does not drop under the condition of 100kHz, and its Curie temperature Tc is unknown.
[0006] Therefore, how to provide a manganese-zinc ferrite material with excellent performance, high magnetic permeability, high Curie temperature, low temperature coefficient, wide temperature and wide frequency, and greatly improve the working stability of manganese-zinc ferrite materials used in the field of automotive electronics or conventional anti-EMI common mode filters has become a problem that needs to be solved urgently. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a manganese-zinc ferrite material and a preparation method thereof. The manganese-zinc ferrite material provided by the present invention has an initial magnetic permeability μi≥12000 in a wide temperature range of 0 to 145°C, has a relatively high initial magnetic permeability, and has a relatively low temperature coefficient within this temperature range; the magnetic permeability does not drop at a high frequency of 300kHz, μi≥9000; the Curie temperature Tc>145°C, has a relatively high Curie temperature, and greatly improves the working stability of the manganese-zinc ferrite material used in the field of automotive electronics or the field of conventional anti-EMI common mode filters.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a manganese-zinc ferrite material, the manganese-zinc ferrite material comprising a main component and an auxiliary component, the main component comprising Fe2O3, ZnO and MnO, the auxiliary component comprising CoO, CaO, Bi2O3 and MoO;
[0010] In the main component, the Fe2O3 content is 52.0-53.0 mol%, by mole percentage, for example, 52.0 mol%, 52.1 mol%, 52.2 mol%, 52.3 mol%, 52.4 mol%, 52.5 mol%, 52.6 mol%, 52.7 mol%, 52.8 mol%, 52.9 mol% or 53.0 mol%, etc.;
[0011] The ZnO content is 18.0-19.0 mol%, for example, 18.0 mol%, 18.1 mol%, 18.2 mol%, 18.3 mol%, 18.4 mol%, 18.5 mol%, 18.6 mol%, 18.7 mol%, 18.8 mol%, 18.9 mol% or 19.0 mol%;
[0012] The MnO content is 28.0-30.5 mol%, for example, 28.0 mol%, 28.1 mol%, 28.2 mol%, 28.3 mol%, 28.4 mol%, 28.5 mol%, 28.6 mol%, 28.7 mol%, 28.8 mol%, 28.9 mol%, 29.0 mol%, 29.1 mol%, 29.2 mol%, 29.3 mol%, 29.4 mol%, 29.5 mol%, 29.6 mol%, 29.7 mol%, 29.8 mol%, 29.9 mol%, 30.0 mol%, 30.1 mol%, 30.2 mol%, 30.3 mol%, 30.4 mol% or 30.5 mol%, etc.
[0013] The manganese-zinc ferrite material provided by the present invention comprises auxiliary components CoO, CaO, Bi2O3 and MoO, wherein the magnetic anisotropy constant K1 of CoO is greater than 0, and the magnetic anisotropy constant K2 of CoO is greater than 0. 2+ After the addition of Fe 2+ Due to the synergistic effect, the K1 value decreases sharply with the increase of temperature, so that the temperature range where the offset point of K1=0 is lower than the Curie temperature Tc is possible; since Bi2O3 and MoO have a low melting point, the two can work together to promote grain growth, and during the sintering process, they can promote the discharge of pores, further improving the uniformity and density of the material structure. In addition, the addition of MoO can also increase the initial magnetic permeability and reduce losses; CaO has a coating effect, which can form a high resistance layer at the grain boundary to increase the grain boundary resistivity, thereby increasing the resistance and improving the frequency characteristics.
[0014] CoO, CaO, Bi2O3 and MoO work together to synergistically improve the various properties of the manganese-zinc ferrite material. The prepared manganese-zinc ferrite material has an initial magnetic permeability μi≥12000 in a wide temperature range of 0-145°C, has a high initial magnetic permeability, and has a low temperature coefficient in this temperature range; the magnetic permeability does not drop at a high frequency of 300kHz, μi≥9000; the Curie temperature Tc>145°C, has a high Curie temperature.
[0015] As a preferred technical solution of the present invention, in the main components, by molar percentage, the Fe2O3 content is 52.2-52.5mol%, the ZnO content is 18.2-18.9mol%, and the MnO content is 28.5-29.8mol%.
[0016] As a preferred technical solution of the present invention, based on the total mass of the main component, the CoO content is 0 to 4000 ppm and is not 0, for example, 10 ppm, 100 ppm, 200 ppm, 500 ppm, 1000 ppm, 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 3500 ppm or 4000 ppm, etc., preferably 0 to 2000 ppm and is not 0.
[0017] Preferably, based on the total mass of the main component, the CaO content is 0 to 2000 ppm and is not 0, for example, 10 ppm, 100 ppm, 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm, 1200 ppm, 1400 ppm, 1600 ppm, 1800 ppm or 2000 ppm, etc., preferably 100 to 2000 ppm.
[0018] Preferably, based on the total mass of the main component, the content of Bi2O3 is 0 to 2000 ppm and is not 0, for example, 10 ppm, 100 ppm, 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm, 1200 ppm, 1400 ppm, 1600 ppm, 1800 ppm or 2000 ppm, etc., preferably 100 to 2000 ppm.
[0019] Preferably, based on the total mass of the main component, the content of MoO is 0 to 2000 ppm and is not 0, for example, 10 ppm, 100 ppm, 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm, 1200 ppm, 1400 ppm, 1600 ppm, 1800 ppm or 2000 ppm, etc., preferably 100 to 2000 ppm.
[0020] In a second aspect, the present invention further provides a method for preparing the manganese-zinc ferrite material according to the first aspect, the preparation method comprising the following steps:
[0021] (1) Fe2O3, ZnO, auxiliary components and complexing agent solution are uniformly mixed, and then a precipitant solution is added to react, and after drying, a first sintering is performed to obtain zinc-iron clinker;
[0022] The auxiliary components include CoO, CaO, Bi2O3 and MoO;
[0023] (2) mixing MnO and the zinc-iron clinker described in step (1) uniformly, performing a second sintering and crushing to obtain a ferrite mixture;
[0024] In the ferrite mixture, the Fe2O3 content is 52.0-53.0 mol%, the ZnO content is 18.0-19.0 mol%, and the MnO content is 28.0-30.5 mol% in molar percentage;
[0025] (3) mixing the binder solution with the ferrite mixture described in step (2) to form granules to obtain ferrite granules;
[0026] (4) Pressing the ferrite particles described in step (3) into shape, and performing a third sintering to obtain a manganese-zinc ferrite material.
[0027] In order to make the nano-scale auxiliary components give full play to their respective characteristics, the present invention adopts a sol-gel method to fully mix Fe2O3 and ZnO as well as the nano-scale auxiliary components, obtains zinc-iron clinker after sintering, and then mixes it evenly with MnO, so as to evenly distribute the auxiliary components among the main components to the greatest extent, thereby realizing the manganese-zinc ferrite material with high magnetic permeability, high Curie temperature, low temperature coefficient, wide temperature range and wide frequency range.
[0028] As a preferred technical solution of the present invention, the mixing in step (1) comprises: firstly ball-milling Fe2O3, ZnO and auxiliary components, and then adding the complexing agent solution and stirring.
[0029] Preferably, based on the total mass of the Fe2O3, ZnO and MnO, the content of CoO in step (1) is 0 to 4000 ppm and not 0, the content of CaO is 0 to 2000 ppm and not 0, the content of Bi2O3 is 0 to 2000 ppm and not 0, and the content of MoO is 0 to 2000 ppm and not 0.
[0030] Preferably, the complexing agent solution in step (1) comprises sodium citrate solution or glucose.
[0031] Preferably, the ball milling speed is 200-400 rpm, for example, 200 rpm, 220 rpm, 250 rpm, 280 rpm, 300 rpm, 320 rpm, 350 rpm, 380 rpm or 400 rpm, and the ball milling time is 1-3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, etc.
[0032] Preferably, the stirring time is 20 to 40 min, for example, 20 min, 25 min, 30 min, 35 min or 40 min.
[0033] As a preferred technical solution of the present invention, the precipitant solution in step (1) includes sodium hydroxide solution or ethylene glycol.
[0034] Preferably, the reaction time of step (1) is 10 to 50 min, for example, 10 min, 20 min, 30 min, 40 min or 50 min.
[0035] Preferably, after the reaction in step (1) is completed and before drying, centrifugation is also included.
[0036] Preferably, the drying temperature in step (1) is 80-160°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or 160°C; and the drying time is 4-6h, for example, 4h, 5h or 6h.
[0037] Preferably, the atmosphere of the first sintering in step (1) is an air atmosphere.
[0038] Preferably, the sintering temperature of the first sintering in step (1) is 800-900°C, for example, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C or 900°C.
[0039] Preferably, the holding time of the first sintering in step (1) is 3 to 5 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours.
[0040] As a preferred technical solution of the present invention, the mixing in step (2) includes wet sand grinding.
[0041] Preferably, the wet sanding time is 60 to 70 min, for example, 60 min, 62 min, 64 min, 66 min, 68 min or 70 min.
[0042] Preferably, after the mixing in step (2) is completed and before the second sintering is performed, drying is also included.
[0043] Preferably, the drying temperature is 80-160°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or 160°C; the drying time is 10-24h, for example, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h.
[0044] Preferably, the atmosphere of the second sintering in step (2) is an air atmosphere.
[0045] Preferably, the sintering temperature of the second sintering in step (2) is 700-850°C, for example, 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C or 850°C.
[0046] Preferably, the holding time of the second sintering in step (2) is 2 to 3 hours, such as 2 hours, 2.5 hours or 3 hours.
[0047] Preferably, the pulverizing in step (2) comprises ball milling, preferably horizontal ball milling.
[0048] Preferably, the ball milling speed is 200-400 rpm, for example, 200 rpm, 220 rpm, 250 rpm, 280 rpm, 300 rpm, 320 rpm, 350 rpm, 380 rpm or 400 rpm, and the ball milling time is 2-4 h, for example, 2 h, 2.5 h, 3 h, 3.5 h or 4 h, etc.
[0049] Preferably, after the pulverization in step (2) and before obtaining the ferrite mixture, drying is also included.
[0050] Preferably, the drying temperature is 80-160°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or 160°C; the drying time is 10-24h, for example, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h.
[0051] As a preferred technical solution of the present invention, the binder solution in step (3) includes a polyvinyl alcohol solution.
[0052] Preferably, the mass fraction of the binder solution in step (3) is 6-9wt%, for example, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt% or 9wt%.
[0053] As a preferred technical solution of the present invention, the pressure of the pressing molding in step (4) is 4 to 10 MPa, for example, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa or 10 MPa.
[0054] Preferably, the third sintering includes a first stage sintering, a second stage sintering and a third stage sintering.
[0055] In the present invention, the first sintering in the third sintering can make the binder added in the granulation process disperse more smoothly, reduce the influence of the binder on the material, and fully remove the impurities and bubbles contained therein. During the second sintering process, the grain boundaries begin to move, and the grains gradually grow, so that the relative density of the material increases rapidly to reach a densification level. Since the preparation of the manganese-zinc ferrite material is an oxidation-reduction process, the third sintering is performed to simultaneously reduce the oxygen content in the sintering atmosphere, which helps to improve the frequency performance of the manganese-zinc ferrite material.
[0056] Preferably, the first stage sintering is carried out in a nitrogen-oxygen mixed gas with an oxygen content of 19-21 vol%, such as 19 vol%, 20 vol% or 21 vol%.
[0057] Preferably, the heating rate of the first stage sintering is 0.2-0.5°C / min, such as 0.2°C / min, 0.3°C / min, 0.4°C / min or 0.5°C / min.
[0058] Preferably, the sintering temperature of the first stage sintering is 550-650°C, for example, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C or 650°C.
[0059] Preferably, the holding time of the first stage sintering is 3 to 4 hours, such as 3 hours, 3.5 hours or 4 hours.
[0060] Preferably, the second stage sintering is carried out in a nitrogen-oxygen mixed gas with an oxygen content of 19-21 vol%, such as 19 vol%, 20 vol% or 21 vol%.
[0061] Preferably, the heating rate of the second stage sintering is 0.5-1°C / min, for example, 0.5°C / min, 0.6°C / min, 0.7°C / min, 0.8°C / min, 0.9°C / min or 1°C / min.
[0062] Preferably, the sintering temperature of the second stage sintering is 1000-1100°C, for example, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C or 1100°C.
[0063] Preferably, the holding time of the second sintering stage is 4 to 8 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours.
[0064] Preferably, the third stage sintering is carried out in a nitrogen-oxygen mixed gas with an oxygen content of 3-8 vol%, such as 3 vol%, 4 vol%, 5 vol%, 6 vol%, 7 vol% or 8 vol%.
[0065] Preferably, the heating rate of the third stage sintering is 1-5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.
[0066] Preferably, the sintering temperature of the third stage sintering is 1250-1375°C, for example, 1250°C, 1260°C, 1270°C, 1280°C, 1290°C, 1300°C, 1310°C, 1320°C, 1330°C, 1340°C, 1350°C, 1360°C, 1370°C or 1375°C.
[0067] Preferably, the holding time of the third sintering stage is 5 to 7 hours, such as 5 hours, 6 hours or 7 hours.
[0068] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0069] (1) determining the Fe2O3 content, ZnO content and MnO content in molar percentage, ball milling Fe2O3, ZnO and auxiliary components at a speed of 200 to 400 rpm for 1 to 3 hours, adding a complexing agent solution and stirring for 20 to 40 minutes, then adding a precipitant solution and reacting for 20 to 40 minutes, drying at 80 to 160° C. for 4 to 6 hours after centrifugation, and then heat-keeping at 800 to 900° C. for 3 to 5 hours in an air atmosphere to perform a first sintering to obtain zinc-iron clinker;
[0070] Wherein, the auxiliary components include CoO, CaO, Bi2O3 and MoO, and based on the total mass of the Fe2O3, ZnO and MnO, the content of the CoO is 0-4000ppm and not 0, the content of the CaO is 0-2000ppm and not 0, the content of the Bi2O3 is 0-2000ppm and not 0, and the content of the MoO is 0-2000ppm and not 0; the complexing agent solution includes sodium citrate solution or glucose; the precipitant solution includes sodium hydroxide solution or ethylene glycol;
[0071] (2) MnO and the zinc-iron clinker described in step (1) are wet-grinded for 60 to 70 minutes, dried at 80 to 160° C. for 10 to 24 hours, and then kept at 700 to 850° C. for 2 to 3 hours in an air atmosphere for a second sintering, ball-milled at a speed of 200 to 400 rpm for 2 to 4 hours, and dried at 80 to 160° C. for 10 to 24 hours to obtain a ferrite mixture;
[0072] Wherein, in the ferrite mixture, in terms of molar percentage, the Fe2O3 content is 52.0-53.0 mol%, the ZnO content is 18.0-19.0 mol%, and the MnO content is 28.0-30.5 mol%;
[0073] (3) mixing 6-9 wt % of the binder solution with the ferrite mixture of step (2), granulating, grinding and sieving to obtain ferrite granules;
[0074] Wherein, the binder solution comprises a polyvinyl alcohol solution;
[0075] (4) The ferrite particles described in step (3) are pressed and formed at 4 to 10 MPa to obtain a formed body, and then a third sintering is performed, wherein the temperature is first increased to 550 to 650°C at a rate of 0.2 to 0.5°C / min in a nitrogen-oxygen mixed gas with an oxygen content of 19 to 21 vol% and kept warm for 3 to 4 hours to perform the first stage of sintering, and then the temperature is increased to 1000 to 1100°C at a rate of 0.5 to 1°C / min in the same atmosphere and kept warm for 4 to 8 hours to perform the second stage of sintering, and the sintering atmosphere is adjusted to a nitrogen-oxygen mixed gas with an oxygen content of 3 to 8 vol%, and the temperature is increased to 1250 to 1375°C at a rate of 1 to 5°C / min and kept warm for 5 to 7 hours to perform the third stage of sintering, and the cooling stage is carried out under a balanced oxygen partial pressure to obtain a manganese-zinc ferrite material.
[0076] Compared with the prior art, the present invention has at least the following beneficial effects:
[0077] 1) The manganese-zinc ferrite material provided by the present invention has an initial magnetic permeability μi≥12000 in a wide temperature range of 0 to 145°C, has a relatively high initial magnetic permeability, and has a relatively low temperature coefficient in this temperature range; the magnetic permeability does not drop at a high frequency of 300kHz, μi≥9000; the Curie temperature Tc>145°C, has a relatively high Curie temperature, and greatly improves the working stability of the manganese-zinc ferrite material used in the field of automotive electronics or the field of conventional anti-EMI common mode filters;
[0078] 2) The present invention achieves the preparation of manganese-zinc ferrite materials with high magnetic permeability, high Curie temperature, low temperature coefficient, wide temperature and wide frequency by regulating the composition of the main component and the auxiliary component and the respective addition amounts, and cooperating with the corresponding preparation method. DETAILED DESCRIPTION
[0079] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0080] Example 1
[0081] The present embodiment provides a manganese-zinc ferrite material and a preparation method thereof, wherein the main component of the manganese-zinc ferrite material has a Fe2O3 content of 52.27 mol%, a ZnO content of 18.52 mol%, and a MnO content of 29.21 mol% in molar percentage; the auxiliary component has a CoO content of 1200 ppm, a CaO content of 200 ppm, a Bi2O3 content of 400 ppm, and a MoO content of 200 ppm based on the total mass of the main component;
[0082] The preparation method comprises the following steps:
[0083] (1) 52.27 mol% Fe2O3, 18.52 mol% ZnO, 1200 ppm CoO, 200 ppm CaO, 400 ppm Bi2O3 and 200 ppm MoO were ball-milled at 256 rpm for 2 h, sodium citrate solution was added and stirred for 30 min, sodium hydroxide solution was added dropwise and reacted for 30 min, centrifuged, dried at 120° C. for 5 h to obtain an intermediate product, and kept at 850° C. for 3 h in an air atmosphere for a first sintering to obtain zinc-iron clinker;
[0084] (2) 29.21 mol% MnO and zinc-iron clinker were wet-grinded for 60 min, dried at 120° C. for 12 h, kept at 700° C. for 3 h in an air atmosphere, subjected to a second sintering, and horizontally ball-milled at a speed of 256 rpm for 2 h, with a ratio of 16 mm diameter to 5.6 mm diameter steel balls being 2:1, with a total mass of 1000 g, and dried at 120° C. for 12 h to obtain a ferrite mixture;
[0085] (3) mixing 8 wt % PVA solution with a ferrite mixture, granulating, grinding and sieving to obtain a ferrite granular material;
[0086] (4) The ferrite particles are pressed and molded at 6 MPa to obtain a molded body with a size of H25×15×8 mm, and the third sintering is performed, wherein the temperature is first increased to 600°C at a rate of 0.5°C / min in a nitrogen-oxygen mixed gas with an oxygen content of 21 vol% and kept warm for 3.5 h to perform the first stage of sintering, and then the temperature is increased to 1100°C at a rate of 0.5°C / min in the same atmosphere and kept warm for 6 h to perform the second stage of sintering, and the sintering atmosphere is adjusted to a nitrogen-oxygen mixed gas with an oxygen content of 5 vol%, and the temperature is increased to 1375°C at a rate of 1.5°C / min and kept warm for 6 h to perform the third stage of sintering, and the temperature is lowered under a balanced oxygen partial pressure to obtain a manganese-zinc ferrite material.
[0087] Example 2
[0088] This embodiment provides a manganese-zinc ferrite material and a preparation method thereof. The manganese-zinc ferrite material is different from that of Embodiment 1 in that, in the main component, the content of Fe2O3 is 52.26 mol%, the content of ZnO is 18.4 mol%, and the content of MnO is 29.34 mol% by mole percentage; in the auxiliary component, based on the total mass of the main component, the content of CoO is 1000 ppm, the content of CaO is 100 ppm, the content of Bi2O3 is 400 ppm, and the content of MoO is 200 ppm;
[0089] The difference between the preparation method and Example 1 is that in step (1) of this embodiment, the ball milling raw materials are 52.26 mol% Fe2O3, 18.4 mol% ZnO, 1000 ppm CoO, 100 ppm CaO, 400 ppm Bi2O3 and 200 ppm MoO, the first sintering temperature is 800°C, in step (2), MnO is 29.34 mol%, in step (4), the third sintering temperature is 1365°C, and the rest of the preparation method and parameters are consistent with Example 1.
[0090] Example 3
[0091] This embodiment provides a manganese-zinc ferrite material and a preparation method thereof. The manganese-zinc ferrite material is different from that in Embodiment 1 in that, in the main component, the content of Fe2O3 is 52.5 mol%, the content of ZnO is 18.5 mol%, and the content of MnO is 29.0 mol% by mole percentage; in the auxiliary component, based on the total mass of the main component, the content of CoO is 1500 ppm, the content of CaO is 100 ppm, the content of Bi2O3 is 400 ppm, and the content of MoO is 200 ppm;
[0092] The difference between the preparation method and Example 1 is that in step (1) of this embodiment, the ball milling raw materials are 52.5 mol% Fe2O3, 18.5 mol% ZnO, 1500 ppm CoO, 100 ppm CaO, 400 ppm Bi2O3 and 200 ppm MoO, in step (2), MnO is 29.0 mol%, in step (4), the temperature of the third sintering stage is 1370°C, and the rest of the preparation method and parameters are consistent with Example 1.
[0093] Example 4
[0094] The present embodiment provides a manganese-zinc ferrite material and a preparation method thereof. The manganese-zinc ferrite material is different from that of the first embodiment in that, in the main component, the content of Fe2O3 is 52.28 mol%, the content of ZnO is 18.82 mol%, and the content of MnO is 28.9 mol% by mole; in the auxiliary component, based on the total mass of the main component, the content of CoO is 2000 ppm, the content of CaO is 100 ppm, the content of Bi2O3 is 200 ppm, and the content of MoO is 100 ppm;
[0095] The difference between the preparation method and Example 1 is that in step (1) of this embodiment, the ball milling raw materials are 52.28 mol% Fe2O3, 18.82 mol% ZnO, 2000 ppm CoO, 100 ppm CaO, 200 ppm Bi2O3 and 100 ppm MoO, the first sintering temperature is 900°C, in step (2), MnO is 28.9 mol%, the second sintering temperature is 800°C, in step (4), the third sintering temperature is 1320°C, and the rest of the preparation method and parameters are consistent with Example 1.
[0096] Example 5
[0097] The present embodiment provides a manganese-zinc ferrite material and a preparation method thereof, wherein the main component of the manganese-zinc ferrite material has a Fe2O3 content of 52.35 mol%, a ZnO content of 18.3 mol%, and a MnO content of 29.35 mol% in molar percentage; the auxiliary component has a CoO content of 500 ppm, a CaO content of 100 ppm, a Bi2O3 content of 100 ppm, and a MoO content of 100 ppm based on the total mass of the main component;
[0098] The preparation method comprises the following steps:
[0099] (1) 52.35 mol% Fe2O3, 18.3 mol% ZnO, 500 ppm CoO, 100 ppm CaO, 100 ppm Bi2O3 and 100 ppm MoO were ball-milled at a speed of 200 rpm for 1 hour, sodium citrate solution was added and stirred for 20 minutes, and then sodium hydroxide solution was added dropwise for 40 minutes, centrifuged, and dried at 80°C for 6 hours to obtain an intermediate product, which was kept at 800°C for 4 hours in an air atmosphere for the first sintering to obtain zinc-iron clinker;
[0100] (2) 29.35 mol% of MnO and zinc-iron clinker were wet-grinded for 65 min, dried at 80° C. for 24 h, kept at 800° C. for 3 h in an air atmosphere, subjected to a second sintering, and horizontally ball-milled at a speed of 400 rpm for 2 h, with a ratio of 16 mm diameter to 5.6 mm diameter steel balls being 2:1, with a total mass of 1000 g, and dried at 80° C. for 24 h to obtain a ferrite mixture;
[0101] (3) mixing 6 wt % PVA solution with a ferrite mixture, granulating, grinding and sieving to obtain a ferrite granular material;
[0102] (4) The ferrite particles are pressed and formed at 4 MPa to obtain a molded body with a size of H25×15×8 mm, and then the third sintering is carried out, wherein the temperature is first increased to 550°C at a rate of 0.2°C / min in a nitrogen-oxygen mixed gas with an oxygen content of 19 vol% and kept warm for 4 hours to carry out the first stage of sintering, and then the temperature is increased to 1050°C at a rate of 0.8°C / min in the same atmosphere and kept warm for 8 hours to carry out the second stage of sintering, and the sintering atmosphere is adjusted to a nitrogen-oxygen mixed gas with an oxygen content of 3 vol%, and the temperature is increased to 1250°C at a rate of 1°C / min and kept warm for 7 hours to carry out the third stage of sintering, and the temperature is lowered under a balanced oxygen partial pressure to obtain a manganese-zinc ferrite material.
[0103] Example 6
[0104] The present embodiment provides a manganese-zinc ferrite material and a preparation method thereof, wherein the main component of the manganese-zinc ferrite material has a Fe2O3 content of 52.45 mol%, a ZnO content of 18.9 mol%, and a MnO content of 28.65 mol% in molar percentage; the auxiliary component has a CoO content of 2000 ppm, a CaO content of 1500 ppm, a Bi2O3 content of 1000 ppm, and a MoO content of 1000 ppm based on the total mass of the main component;
[0105] The preparation method comprises the following steps:
[0106] (1) 52.45 mol% Fe2O3, 18.9 mol% ZnO, 2000 ppm CoO, 1500 ppm CaO, 1000 ppm Bi2O3 and 1000 ppm MoO were ball-milled at 400 rpm for 1 hour, sodium citrate solution was added and stirred for 40 minutes, and then sodium hydroxide solution was added dropwise for 20 minutes, centrifuged, and dried at 160° C. for 4 hours to obtain an intermediate product, which was kept at 900° C. for 3 hours in an air atmosphere for the first sintering to obtain zinc-iron clinker;
[0107] (2) 28.65 mol% of MnO and zinc-iron clinker were wet-grinded for 70 min, dried at 160° C. for 10 h, kept at 700° C. for 2 h in an air atmosphere, subjected to a second sintering, and horizontally ball-milled at a speed of 200 rpm for 4 h, with a ratio of 16 mm diameter to 5.6 mm diameter steel balls being 2:1, with a total mass of 1000 g, and dried at 160° C. for 10 h to obtain a ferrite mixture;
[0108] (3) grinding, sieving and stirring the 9 wt % PVA solution and the ferrite mixture, and then granulating to obtain ferrite granules;
[0109] (4) The ferrite particles are pressed and molded at 10 MPa to obtain a molded body with a size of H25×15×8 mm, and then the third sintering is performed, wherein the temperature is first increased to 650°C at a rate of 0.3°C / min in a nitrogen-oxygen mixed gas with an oxygen content of 20 vol% and kept warm for 3 hours to perform the first stage of sintering, and then the temperature is increased to 1000°C at a rate of 1°C / min in the same atmosphere and kept warm for 4 hours to perform the second stage of sintering, and the sintering atmosphere is adjusted to a nitrogen-oxygen mixed gas with an oxygen content of 8 vol%, and the temperature is increased to 1360°C at a rate of 5°C / min and kept warm for 5 hours to perform the third stage of sintering, and the temperature is lowered under a balanced oxygen partial pressure to obtain a manganese-zinc ferrite material.
[0110] Example 7
[0111] This embodiment provides a manganese-zinc ferrite material and a preparation method thereof. The difference between the manganese-zinc ferrite material and the embodiment 1 is that the CoO content in the auxiliary component is 2200ppm, and the other components and contents are consistent with the embodiment 1;
[0112] The difference between the preparation method and Example 1 is that in step (1) the CoO content in the ball-milled raw material is 2200 ppm, and the rest of the preparation method and parameters are consistent with Example 1.
[0113] Example 8
[0114] This embodiment provides a manganese-zinc ferrite material and a preparation method thereof. The difference between this embodiment and embodiment 1 is that in step (4), the temperature of the third sintering stage is 1230° C., and the rest of the preparation methods and parameters are consistent with those of embodiment 1.
[0115] Example 9
[0116] This embodiment provides a manganese-zinc ferrite material and a preparation method thereof. The difference between this embodiment and embodiment 1 is that in step (4), the temperature of the third sintering stage is 1395° C., and the rest of the preparation methods and parameters are consistent with those of embodiment 1.
[0117] Example 10
[0118] The present embodiment provides a manganese-zinc ferrite material and a preparation method thereof. The difference between the present embodiment and embodiment 1 is that, in step (4), the atmosphere of the third sintering is consistent with the atmosphere of the first sintering and the second sintering, that is, the third sintering is carried out in a nitrogen-oxygen mixed gas with an oxygen content of 21 vol%. The rest of the preparation methods and parameters are consistent with those in embodiment 1.
[0119] Embodiment 11
[0120] This embodiment provides a manganese-zinc ferrite material and a preparation method thereof. The difference between this embodiment and embodiment 1 is that in step (4), the second sintering process is omitted, that is, only the first sintering and the third sintering are performed, and the rest of the preparation methods and parameters are consistent with those of embodiment 1.
[0121] Example 12
[0122] This embodiment provides a manganese-zinc ferrite material and a preparation method thereof. The components and contents of the manganese-zinc ferrite material provided in this embodiment are the same as those in Example 1. The preparation method comprises the following steps:
[0123] (1) 52.27 mol% Fe2O3, 18.52 mol% ZnO and 29.21 mol% MnO were ball-milled at 256 rpm for 2 h, dried at 120°C for 12 h, and kept at 880°C for 3 h for the first sintering to obtain a mixed powder;
[0124] (2) adding 1200 ppm CoO, 200 ppm CaO, 400 ppm Bi2O3 and 200 ppm MoO to the mixed powder, ball milling the mixture at a speed of 256 rpm for 80 min, spray granulating and sieving to obtain ferrite particles;
[0125] (3) The ferrite particles are pressed and molded at 6 MPa to obtain a molded body with a size of H25×15×8, and then a second sintering is performed, wherein the temperature is first increased to 1330°C at a rate of 1.2°C / min in a nitrogen-oxygen mixed gas with an oxygen content of 21 vol% and kept at this temperature for 7 hours, and the first stage of sintering is performed. The sintering atmosphere is adjusted to a nitrogen-oxygen mixed gas with an oxygen content of 5 vol% and the temperature is increased to 1370°C at a rate of 1.5°C / min and kept at this temperature for 1.5 hours, and the second stage of sintering is performed. The temperature is then lowered under a balanced oxygen partial pressure to obtain a manganese-zinc ferrite material.
[0126] Comparative Example 1
[0127] This comparative example provides a manganese-zinc ferrite material and a preparation method thereof. The difference between the manganese-zinc ferrite material and Example 1 is that CoO in the auxiliary component is replaced by Ta2O5 of the same content, and MoO is replaced by In2O3 of the same content, and the remaining components and contents are consistent with Example 1;
[0128] The difference between the preparation method and Example 1 is that in step (1) of ball-milling the raw material, CoO in the auxiliary component is replaced by Ta2O5 with an equal content, and MoO is replaced by In2O3 with an equal content. The rest of the preparation method and parameters are consistent with Example 1.
[0129] Comparative Example 2
[0130] This comparative example provides a manganese-zinc ferrite material and a preparation method thereof. The difference between the manganese-zinc ferrite material and Example 1 is that CoO in the auxiliary component is replaced with an equal content of V2O5, and the other components and contents are consistent with Example 1;
[0131] The difference between the preparation method and Example 1 is that in step (1) of ball-milling the raw material, CoO in the auxiliary component is replaced with an equal content of V2O5, and the rest of the preparation method and parameters are consistent with those of Comparative Example 1.
[0132] Comparative Example 3
[0133] This comparative example provides a manganese-zinc ferrite material and a preparation method thereof. The manganese-zinc ferrite material is different from Example 1 in that MoO and CaO are omitted, that is, the auxiliary components are CoO and Bi2O3, and the remaining components and contents are consistent with those in Example 1;
[0134] The difference between the preparation method and Example 1 is that in step (1), MoO and CaO are omitted from the ball-milled raw material, and the rest of the preparation method and parameters are consistent with Example 1.
[0135] Comparative Example 4
[0136] This comparative example provides a manganese-zinc ferrite material and a preparation method thereof. The difference between the manganese-zinc ferrite material and Example 1 is that CoO is omitted, that is, the auxiliary components are MoO, CaO and Bi2O3, and the remaining components and contents are consistent with those in Example 1;
[0137] The difference between the preparation method and Example 1 is that in step (1) of ball-milling the raw material, CoO is omitted, and the rest of the preparation method and parameters are the same as those in Example 1.
[0138] Comparative Example 5
[0139] This comparative example provides a manganese-zinc ferrite material and a preparation method thereof. The manganese-zinc ferrite material is different from Example 1 in that, in the main component, the content of Fe2O3 is 52.35 mol%, the content of ZnO is 16.36 mol%, the content of MnO is 31.29 mol%, and the remaining components and contents are consistent with Example 1;
[0140] The difference between the preparation method and Example 1 is that in step (1), the ball milling raw materials are 52.35 mol% Fe2O3 and 16.36 mol% ZnO, and in step (2), MnO is 31.29 mol%. The remaining preparation methods and parameters are consistent with Example 1.
[0141] Comparative Example 6
[0142] This comparative example provides a manganese-zinc ferrite material and a preparation method thereof. The difference between the manganese-zinc ferrite material and Example 1 is that, in the main component, the content of Fe2O3 is 52.35 mol%, the content of ZnO is 24.79 mol%, the content of MnO is 22.86 mol%, and the remaining components and contents are consistent with those in Example 1;
[0143] The difference between the preparation method and Example 1 is that in step (1), the ball milling raw materials are 52.35 mol% Fe2O3 and 24.79 mol% ZnO, and in step (2), MnO is 22.86 mol%. The remaining preparation methods and parameters are consistent with Example 1.
[0144] The manganese-zinc ferrite materials prepared in Examples 1 to 12 and Comparative Examples 1 to 6 were subjected to magnetic permeability tests and Curie temperature tests under different kHz conditions (test temperature was 25°C), and the specific test results are shown in Table 1, as well as magnetic permeability tests under different temperature conditions (10kHz, 0.25V), and the specific test results are shown in Table 2.
[0145] Table 1
[0146]
[0147]
[0148] Table 2
[0149]
[0150]
[0151] The test results show that:
[0152] (1) It can be seen from Examples 1-6 that the present invention can achieve high magnetic permeability, excellent frequency characteristics and temperature characteristics of manganese-zinc ferrite materials by regulating the composition of the main component and the auxiliary component and the respective addition amounts, and then combining the corresponding preparation process, that is, preparing the iron-zinc mixture by the sol-gel process, and then mixing it with manganese oxide and adopting a sintering process. In the wide temperature range of 0 to 145°C, the initial magnetic permeability μi ≥ 12000, with a high initial magnetic permeability, and in this temperature range, it has a low temperature coefficient; the magnetic permeability at a high frequency of 300kHz does not drop, μi ≥ 9000; the Curie temperature Tc> 145°C, with a high Curie temperature;
[0153] (2) It can be seen from Example 1 and Example 7 that the present invention can better achieve the effect of significantly improving the Curie temperature by regulating the CoO content in the range of 0 to 2000 ppm (not 0); if the CoO content is too high, the material loss will increase, the initial magnetic permeability will decrease, and the material inhomogeneity will increase, and the Curie temperature will decrease; if the CoO content is too low, its optimization effect on magnetic properties cannot be fully exerted, and thus the effect of improving various material properties cannot be achieved;
[0154] (3) It can be seen from Examples 1 and 8 to 10 that, on the basis of obtaining a dense material, the present invention further adjusts the temperature of the third stage sintering to 1250 to 1375°C and reduces the oxygen content in the sintering atmosphere, which can better improve the frequency performance of the manganese-zinc ferrite material; if the temperature of the third stage sintering is too high or too low and the corresponding oxygen content in the sintering atmosphere is too high, it will affect the internal structure of the material and reduce the Curie temperature, resulting in a magnetic permeability of 0 at a high temperature (145°C);
[0155] (4) It can be seen from Example 1 and Example 11 that the present invention can control the growth of microstructure through the second stage sintering to achieve the compactness of the manganese-zinc ferrite material. If the second stage sintering is omitted, the compactness of the material is reduced, and the effect of improving the various properties of the material cannot be achieved.
[0156] (5) It can be seen from Example 1 and Example 12 that the present invention combines the sol-gel process with the mixed sintering process. Compared with the traditional single mixed sintering process, the auxiliary components can be evenly distributed between the main components to the greatest extent, and the role of the auxiliary components can be maximized, thereby achieving the manganese-zinc ferrite material with high magnetic permeability, high Curie temperature, low temperature coefficient, wide temperature and wide frequency;
[0157] (6) It can be seen from Example 1 and Comparative Examples 1-2 that the auxiliary components of the present invention, namely CoO, CaO, Bi2O3 and MoO, can work together to synergistically improve the various properties of the manganese-zinc ferrite material; otherwise, the material will have a negative temperature coefficient, and as the temperature increases, the magnetic permeability decreases and the magnetism weakens;
[0158] (7) It can be seen from Example 1 and Comparative Examples 3-4 that if any one or two of the auxiliary components of the present invention are omitted, the effect of improving the various properties of the manganese-zinc ferrite material cannot be achieved;
[0159] (8) It can be seen from Example 1 and Comparative Examples 5 to 6 that the manganese-zinc ferrite material prepared by regulating the content of ZnO and MnO in the main components of the present invention has better frequency performance. If the content of ZnO and MnO is too high or too low, it will affect the magnetic permeability and the position of the second peak, and the temperature coefficient is poor, and the Curie temperature Tc is also significantly reduced.
[0160] In summary, the present invention provides a manganese-zinc ferrite material, which has an initial magnetic permeability μi≥12000 in a wide temperature range of 0 to 145°C, has a relatively high initial magnetic permeability, and has a relatively low temperature coefficient within this temperature range; the magnetic permeability does not drop at a high frequency of 300kHz, μi≥9000; the Curie temperature Tc>145°C, has a relatively high Curie temperature, and greatly improves the working stability of the manganese-zinc ferrite material used in the field of automotive electronics or the field of conventional anti-EMI common mode filters.
[0161] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A manganese-zinc ferrite material, characterized in that: The manganese-zinc ferrite material includes a main component and an auxiliary component, the main component includes Fe2O3, ZnO and MnO, and the auxiliary component includes CoO, CaO, Bi2O3 and MoO; In the main components, in terms of molar percentage, the content of Fe2O3 is 52.0-53.0 mol%, the content of ZnO is 18.0-19.0 mol%, and the content of MnO is 28.0-30.5 mol%.
2. The manganese-zinc ferrite material according to claim 1, characterized in that: In the main components, in terms of molar percentage, the Fe2O3 content is 52.2-52.5 mol%, the ZnO content is 18.2-18.9 mol%, and the MnO content is 28.5-29.8 mol%.
3. The manganese-zinc ferrite material according to claim 1 or 2, characterized in that: Based on the total mass of the main component, the content of CoO is 0 to 4000 ppm and is not 0, preferably 0 to 2000 ppm and is not 0; Preferably, based on the total mass of the main component, the content of CaO is 0 to 2000 ppm and is not 0, preferably 100 to 2000 ppm; Preferably, based on the total mass of the main component, the content of Bi2O3 is 0 to 2000 ppm and is not 0, preferably 100 to 2000 ppm; Preferably, based on the total mass of the main component, the content of MoO is 0 to 2000 ppm and is not 0, and is preferably 100 to 2000 ppm.
4. A method for preparing the manganese-zinc ferrite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Fe2O3, ZnO, auxiliary components and complexing agent solution are uniformly mixed, and then a precipitant solution is added to react, and after drying, a first sintering is performed to obtain zinc-iron clinker; The auxiliary components include CoO, CaO, Bi2O3 and MoO; (2) mixing MnO and the zinc-iron clinker described in step (1) uniformly, performing a second sintering and crushing to obtain a ferrite mixture; In the ferrite mixture, the Fe2O3 content is 52.0-53.0 mol%, the ZnO content is 18.0-19.0 mol%, and the MnO content is 28.0-30.5 mol% in molar percentage; (3) mixing the binder solution with the ferrite mixture described in step (2) to form granules to obtain ferrite granules; (4) Pressing the ferrite particles described in step (3) into shape, and performing a third sintering to obtain a manganese-zinc ferrite material.
5. The preparation method according to claim 4, characterized in that: The mixing in step (1) comprises: firstly ball-milling Fe2O3, ZnO and auxiliary components, and then adding the complexing agent solution and stirring; Preferably, based on the total mass of the Fe2O3, ZnO and MnO, the content of CoO in step (1) is 0 to 4000 ppm and not 0, the content of CaO is 0 to 2000 ppm and not 0, the content of Bi2O3 is 0 to 2000 ppm and not 0, and the content of MoO is 0 to 2000 ppm and not 0; Preferably, the complexing agent solution in step (1) comprises sodium citrate solution or glucose; Preferably, the ball milling speed is 200-400 rpm, and the ball milling time is 1-3 h.
6. The preparation method according to claim 4 or 5, characterized in that: The precipitant solution in step (1) comprises sodium hydroxide solution or ethylene glycol; Preferably, the reaction time in step (1) is 10 to 50 minutes; Preferably, the atmosphere of the first sintering in step (1) is an air atmosphere; Preferably, the sintering temperature of the first sintering in step (1) is 800-900° C.; Preferably, the holding time of the first sintering in step (1) is 3 to 5 hours.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The mixing in step (2) includes wet sand grinding; Preferably, the wet sanding time is 60 to 70 minutes; Preferably, the atmosphere of the second sintering in step (2) is an air atmosphere; Preferably, the sintering temperature of the second sintering in step (2) is 700-850° C.; Preferably, the holding time of the second sintering in step (2) is 2 to 3 hours; Preferably, the pulverizing in step (2) comprises ball milling, preferably horizontal ball milling; Preferably, the ball milling speed is 200-400 rpm, and the ball milling time is 2-4 hours.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The binder solution in step (3) includes a polyvinyl alcohol solution; Preferably, the mass fraction of the binder solution in step (3) is 6 to 9 wt %.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The pressure of the compression molding in step (4) is 4 to 10 MPa; Preferably, the third sintering includes a first stage sintering, a second stage sintering and a third stage sintering; Preferably, the first stage sintering is carried out in a nitrogen-oxygen mixed gas having an oxygen content of 19 to 21 vol%; Preferably, the heating rate of the first stage sintering is 0.2-0.5°C / min; Preferably, the sintering temperature of the first stage sintering is 550-650°C; Preferably, the holding time of the first sintering stage is 3 to 4 hours; Preferably, the second stage sintering is carried out in a nitrogen-oxygen mixed gas having an oxygen content of 19 to 21 vol%; Preferably, the heating rate of the second stage sintering is 0.5-1°C / min; Preferably, the sintering temperature of the second stage sintering is 1000-1100°C; Preferably, the holding time of the second sintering stage is 4 to 8 hours; Preferably, the third stage sintering is carried out in a nitrogen-oxygen mixed gas with an oxygen content of 3 to 8 vol%; Preferably, the heating rate of the third stage sintering is 1-5°C / min; Preferably, the sintering temperature of the third stage sintering is 1250-1375°C; Preferably, the holding time of the third sintering stage is 5 to 7 hours.
10. The preparation method according to any one of claims 4 to 9, characterized in that: The preparation method comprises the following steps: (1) determining the Fe2O3 content, ZnO content and MnO content in molar percentage, ball milling Fe2O3, ZnO and auxiliary components at a speed of 200 to 400 rpm for 1 to 3 hours, adding a complexing agent solution and stirring for 20 to 40 minutes, then adding a precipitant solution and reacting for 10 to 50 minutes, drying at 80 to 160° C. for 4 to 6 hours after centrifugation, and then heat-keeping at 800 to 900° C. for 3 to 5 hours in an air atmosphere to perform a first sintering to obtain zinc-iron clinker; Wherein, the auxiliary components include CoO, CaO, Bi2O3 and MoO; based on the total mass of the Fe2O3, ZnO and MnO, the content of CoO is 0-4000ppm and not 0, the content of CaO is 0-2000ppm and not 0, the content of Bi2O3 is 0-2000ppm and not 0, and the content of MoO is 0-2000ppm and not 0; the complexing agent solution includes sodium citrate solution or glucose; the precipitant solution includes sodium hydroxide solution or ethylene glycol; (2) MnO and the zinc-iron clinker described in step (1) are wet-grinded for 60 to 70 minutes, dried at 80 to 160° C. for 10 to 24 hours, and then kept at 700 to 850° C. for 2 to 3 hours in an air atmosphere for a second sintering, ball-milled at a speed of 200 to 400 rpm for 2 to 4 hours, and dried at 80 to 160° C. for 10 to 24 hours to obtain a ferrite mixture; Wherein, in the ferrite mixture, in terms of molar percentage, the Fe2O3 content is 52.0-53.0 mol%, the ZnO content is 18.0-19.0 mol%, and the MnO content is 28.0-30.5 mol%; (3) mixing 6-9 wt % of the binder solution with the ferrite mixture of step (2), granulating, grinding and sieving to obtain ferrite granules; Wherein, the binder solution comprises a polyvinyl alcohol solution; (4) The ferrite particles described in step (3) are pressed and formed at 4 to 10 MPa to obtain a formed body, and then a third sintering is performed, wherein the temperature is first increased to 550 to 650°C at a rate of 0.2 to 0.5°C / min in a nitrogen-oxygen mixed gas with an oxygen content of 19 to 21 vol% and kept warm for 3 to 4 hours to perform the first stage of sintering, and then the temperature is increased to 1000 to 1100°C at a rate of 0.5 to 1°C / min in the same atmosphere and kept warm for 4 to 8 hours to perform the second stage of sintering, and the sintering atmosphere is adjusted to a nitrogen-oxygen mixed gas with an oxygen content of 3 to 8 vol%, and the temperature is increased to 1250 to 1375°C at a rate of 1 to 5°C / min and kept warm for 5 to 7 hours to perform the third stage of sintering, and the cooling stage is carried out under a balanced oxygen partial pressure to obtain a manganese-zinc ferrite material.
Citation Information
Patent Citations
High-permeability, high-frequency, high-impedance and high-Curie-temperature manganese-zinc ferrite material and preparation method thereof
CN112321293A
Mn-Zn ferrite material and preparation method thereof
CN113443906A
Manganese-zinc ferrite material with wide temperature range and high magnetic permeability as well as preparation method and application of manganese-zinc ferrite material
CN117735972A
Wide-temperature low-loss high-strength mnzn power ferrite, and preparation method therefor and use thereof
WO2023093123A1
Manganese-zinc ferrite material and preparation method therefor
WO2024082623A1
Cited By
Soft magnetic ferrite material with wide temperature range, low temperature coefficient and high magnetic conductivity
CN121085626A
High-permeability and high-impedance manganese zinc ferrite material for high frequency and preparation method thereof
CN121913773A
